2022
DOI: 10.3389/fgene.2022.909131
|View full text |Cite
|
Sign up to set email alerts
|

Identified novel heterozygous HTRA1 pathogenic variants in Chinese patients with HTRA1-associated dominant cerebral small vessel disease

Abstract: Background: Homozygous and compound heterozygous mutations in HTRA1 cause cerebral autosomal recessive arteriopathy with subcortical infarcts and leukoencephalopathy (CARASIL). Recently, heterozygous pathogenic variants in HTRA1 were described in patients with autosomal dominant cerebral small vessel disease (CSVD). Here, we investigated the genetic variants in a cohort of Chinese patients with CSVD.Methods: A total of 95 Chinese index patients with typical characteristics of CSVD were collected. Whole exome s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Extra-neurological symptoms also vary between the diseases. Several investigations indicated high occurrences of early-onset alopecia (20%~30%) and spondylosis (70%~100%) (Chen et al, 2022;Lee et al, 2018;Nozaki et al, 2016) in HTRA1-autosomal dominant disease, while others reported absence of such symptoms (Di Donato et al, 2017;Verdura et al, 2015). Nonetheless, the overall proportion of extra-neurological features of HTRA1-autosomal dominant disease is still lower than CARASIL, which demonstrates alopecia in more than 90% of patients and spinal lesions in almost 100% of patients (Mancuso et al, 2020).…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Extra-neurological symptoms also vary between the diseases. Several investigations indicated high occurrences of early-onset alopecia (20%~30%) and spondylosis (70%~100%) (Chen et al, 2022;Lee et al, 2018;Nozaki et al, 2016) in HTRA1-autosomal dominant disease, while others reported absence of such symptoms (Di Donato et al, 2017;Verdura et al, 2015). Nonetheless, the overall proportion of extra-neurological features of HTRA1-autosomal dominant disease is still lower than CARASIL, which demonstrates alopecia in more than 90% of patients and spinal lesions in almost 100% of patients (Mancuso et al, 2020).…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Most pathogenic and likely pathogenic heterozygous HTRA1 gene variants of symptomatic carriers were missense variants, and some of them were nonsense variants, 30–35 frameshift variants, 27 , 30 , 36 and splice site variants. 6 , 36 , 37 The variant sites of the heterozygous HTRA1 gene were mostly located in exon 4 (50.91%), and the trypsin-like serine protease domain was the most common domain in HtrA1 protease (61.82%). Moreover, we found two variant site aggregation regions (166–182 aa and 276–302 aa).…”
Section: Introductionmentioning
confidence: 99%